Optimal pricing with intermodal competition - Braeutigam, Ronald R. (American Economic Review, 2022)
This analysis extends the work of William Baumol and David Bradford, on efficient pricing with a multiproduct monopoly, to include the case of intermodal competition. A set of rules is developed, showing how second best processes deviate from marginal cost when economics of scale are present. The paper shows why these rules may be difficult to implement in some cases, with a direct application to surface freight transport and then suggests a variation in the theory of second best that may be useful given those difficulties.